2005
DOI: 10.1080/00365520510011641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of regular physical activity on defecation pattern in middle-aged patients complaining of chronic constipation

Abstract: In middle-aged inactive subjects with symptoms of chronic constipation, it is advisable to promote regular physical activity since it improves both the defecation pattern and rectosigmoid or total colonic transit time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(89 citation statements)
references
References 17 publications
3
71
1
8
Order By: Relevance
“…Constipation is a possible risk factor of colon cancer, (35)(36)(37)(38) and this can be relieved by exercise. (39)(40)(41)(42) High physical activity has been reported to be related to low prevalence of constipation in some, (43,44) but not all, studies. (45) One possibility that deserves further consideration is that there could be an association between exercise and sunlight, and therefore vitamin D levels, thought to be protective against neoplasia in the colon and rectum.…”
Section: Discussionmentioning
confidence: 99%
“…Constipation is a possible risk factor of colon cancer, (35)(36)(37)(38) and this can be relieved by exercise. (39)(40)(41)(42) High physical activity has been reported to be related to low prevalence of constipation in some, (43,44) but not all, studies. (45) One possibility that deserves further consideration is that there could be an association between exercise and sunlight, and therefore vitamin D levels, thought to be protective against neoplasia in the colon and rectum.…”
Section: Discussionmentioning
confidence: 99%
“…One small, nonplacebo RCT reported that regular exercise decreases constipation as per Rome I criteria, 88 whereas another even smaller study did not show any benefit. 89 Two other cohort studies showed that physical activity significantly decreased the self-reported symptoms in women.…”
Section: Exercisementioning
confidence: 99%
“…Physical activity appears to accelerate colonic transit time (5)(6)(7), suggesting that exercise may reduce exposure to fecal carcinogens in the colon. Also, effects of exercise related to insulin levels (8,9), insulin-like growth factors, bile acids, and prostaglandins have been proposed (4).…”
Section: Introductionmentioning
confidence: 99%